Co-creating VAlue through Business to Business Experiences - Lockwood, Joseph Benjamin (2010)
Aim of the Project The transformation of the value creating process presents firms with questions on the roles of supplier and consumer and creates a space for exploration of the tensions inherent in these interactions. This management project seeks to add to the debate by investigating how an SME and a selected customer are interacting to create value.